Marx at the movies revisiting history, theory and practice - Mazierska, Ewa.; Kristensen, Lars.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Marx and the Moving Image approaches cinema from a Marxist perspective. It argues that the supposed'end of history', marked by the comprehensive triumph of capitalism and the'end of cinema', calls for revisiting Marx's writings in order to analyse film theories, histories and practices.
Keywords: Science; Science; Science, general